Studies in law, politics and society. Vol. 29 - Sarat, Austin; Ewick, Patricia (Amsterdam : London : JAI, 2003)
This volume presents a diverse array of articles by an interdisciplinary group of scholars. Their work spans the social sciences, humanities, and law, and examines law and culture, the complex intersections of law and policy, and the place of religious values in legal life. The articles published here exemplify the exciting and innovative work now being done in interdisciplinary legal scholarship.
Law and cultural life. Theorizing the public domain : copyright and the development of a cultural commons / Debora Halbert -- The law and the anomaly of performance : baseball as cultural policy / Lara D. Nielsen. Law in domains of policy. Capital punishment and elite politics : dissensus and the death penalty in America / Judith Randle -- Welfare, democracy, and the reflexive legitimacy of the law / Kevin Olson -- Social class, drugs, gender and the limitations of the law : contrasting the elite prostitute with the street prostitute / Maureen A. Norton-Hawk. The place of religious values in legal life. The case for insincerity / John M. Kang.
Description based on print version record.
Keywords: Sociological jurisprudence; Political sociology; Law & society; Law -- General